Contribution of long-lived plasma cells to antibody-mediated allograft rejection - Eunkyeong Jang; Jeehee Youn (Clinical Transplantation and Research)
Persistent alloantigens derived from allograft tissues can be recognized by the host’s alloreactive immune system. This process enables cognate B cells to differentiate into plasma cells, which secrete donor-specific antibodies that are key drivers of antibody-mediated allograft rejection. A subset of these plasma cells can survive for extended periods in a suitable survival niche and mature into long-lived plasma cells (LLPCs), which are a cellular component of humoral memory. The current understanding of LLPCs is limited due to their scarcity, heterogeneity, and absence of unique markers. However, accumulating evidence indicates that LLPCs, unlike conventional short-lived plasma cells, can respond to extrinsic signals from their survival niches and can resist cell death associated with intracellular stress through cell-intrinsic mechanisms. Notably, they are refractory to traditional immunosuppressants and B cell depletion therapies. This resistance, coupled with their longevity, may explain why current treatments targeting antibody-mediated rejection are often ineffective. This review offers insights into the biology of LLPCs and discusses ongoing therapeutic trials that target LLPCs in the context of antibody-mediated allograft rejection.